GASTROPROTECTIVE AND REPARATIVE EFFECTS OF Alstonia boonei AGAINST ASPIRIN-INDUCED GASTROENTEROPATHY IN RAT’S MODEL - Ogeyemhe, Blessing Emosho; Odigie, Efosa Bolaji (FUDMA Journal of Sciences, 2026)
Nonsteroidal anti-inflammatory drugs such as aspirin are widely used but are limited by their potential to induce gastrointestinal injury through oxidative stress, inflammation, and epithelial disruption. This study investigated the protective effects of Alstonia boonei against aspirin-induced gastroenteropathy by evaluating body and organ weights, oxidative stress markers, gross gastric lesions, and histopathological changes in the esophagus, stomach, and duodenum. Rats administered aspirin exhibited reduced weight gain, increased gastric and duodenal organ weights, elevated malondialdehyde levels, depletion of glutathione, and a markedly increased gastric lesion index. These changes were accompanied by severe mucosal alterations, including inflammatory infiltration, glandular distortion, villous disruption, and early erosive damage. Administration of A. boonei alone produced no adverse effects and maintained normal physiological and histological profiles, confirming its safety. Co-treatment with A. boonei resulted in progressive, dose-dependent protection against aspirin-induced injury. Improvements included restoration of weight gain, reduction of organ weight abnormalities, attenuation of oxidative stress, and significant decreases in gross gastric lesions. Histologically, the extract preserved epithelial integrity, reduced inflammatory cell infiltration, and supported normal glandular and villous architecture, with the most pronounced recovery observed at 1500–2000 mg/kg. At these doses, mucosal features approached those of the control group, indicating near-complete structural and biochemical restoration. Overall, the findings demonstrate that A. boonei confers substantial gastroprotective effects through antioxidant and anti-inflammatory mechanisms that stabilize gastrointestinal tissues and counteract aspirin-mediated injury. The extract shows promise as a natural therapeutic agent for mitigating NSAID-induced gastrointestinal damage and warrants further investigation.
Keywords: Alstonia boonei; Aspirin-induced gastroenteropathy; NSAID gastropathy